Cue relevance during navigation is a function of scale and experience - Aaron R. Krochmal; Timothy C. Roth; Nathaniel T. Simmons (Animal Behaviour, 2025)

Distinct fungal and bacterial responses to fire severity and soil depth across a ten-year wildfire chronosequence in beetle-killed lodgepole pine forests - Marcos V. Caiafa; Amelia R. Nelson; Thomas Borch; Holly K. Roth; Timothy S. Fegel; Charles C. Rhoades; Michael J. Wilkins; Sydney I. Glassman (Forest Ecology and Management, 2023)

Wild Australian magpies learn to pull intact, not broken, strings to obtain food - Robin D. Johnsson; Papillon S. Veillet; Farley Connelly; John A. Endler; Timothy C. Roth; John A. Lesku (Behavioral Ecology and Sociobiology, 2023)
The string-pulling paradigm is an approach commonly used in the study of animal cognition to investigate problem-solving abilities. This test involves an out-of-reach reward that can only be acquired through pulling a string. Australian magpies ( Gymnorhina tibicen tyrannica ) can solve cognitive tasks requiring associative and reversal learning, spatial memory, and inhibitory control. Nonetheless, whether magpies can pass a test of means-end understanding—the string-pull test—is unclear. We tested wild magpies on a string-pulling task with five configurations, including a long loose string that required several pulls to obtain food, a short string that only required a single pull to complete, and two short strings—one intact and connected to the food reward; the other broken and unable to yield food when pulled. Of the 11 magpies tested, none solved the long string task at first presentation. Two naïve birds and three, subsequently trained, birds succeeded at the short string. Once proficient at the short string, four of these five birds then solved the long string task; in addition, three learned to choose a functional, intact string over a non-functional, broken string. Overall, these observations provide evidence that Australian magpies have the ability to solve string-pulling tasks but it remains unclear whether they do so by trial-and-error or if they possess means-end understanding. Significance statement We found, for the first time, that wild, free-ranging Australian magpies can learn to solve different versions of a string-pulling task; a version with a short string, a long string, and two strings next to each other where one of them was broken and non-functional (broken string task). Some magpies spontaneously solved the task with the short string, where other magpies required training, and magpies only managed to solve the task with the long string after they had succeeded on the short string task. Furthermore, some of the magpies solved the broken string task but required a high number of trials to do so. Overall, our findings show that Australian magpies have the ability to solve string-pulling tasks but it remains unclear whether they do so by trial-and-error or if they understand causal relations between objects.

The case for investigating the cognitive map in nonavian reptiles - Aaron R. Krochmal; Timothy C. Roth (Animal Behaviour, 2023)

Alcohol Hangover, Sleep Quality, and Daytime Sleepiness - Marith van Schrojenstein Lantman; Thomas Roth; Timothy Roehrs; Joris C. Verster (Sleep and Vigilance, 2017)

The predatory behavior of wintering Accipiter hawks: temporal patterns in activity of predators and prey - Timothy C. Roth; Steven L. Lima (Oecologia, 2007)

Determinants of predation risk in small wintering birds: the hawk’s perspective - Timothy C. Roth; Steven L. Lima; William E. Vetter (Behavioral Ecology and Sociobiology, 2006)